Measurement Of Engagement And Cortical Reorganization In Brains Of Stroke Patients Via Electroencephalography (EEG) As A Result Of Visual Feedback Therapy - Law, Khuan Foo (Universiti Sains Malaysia, 2018)
In line with recent advancement in medical field, there are various innovations in the stroke rehabilitation field in order to reduce the boredom of patients while enhancing their participation in the repetitive rehab exercises. This includes the visual feedback therapy. Besides, the measurement of the state of brains before and after rehab is important in monitoring the recovery of patients. This research covers two major aspects, the influence of the goal-oriented visual feedback rehab system on the engagement of stroke patients in their rehabilitation exercises, as well as the design of brain functional recovery quantification algorithm via Electroencephalography (EEG). EMOTIV EPOC+ is the EEG device used in this research to quantify engagement index as well as the brain functional recovery through its recorded EEG signals. An experiment is carried out on five healthy subjects using an iLLSRM rehab machine with and without visual feedback display. Engagement index (EI) is measured using formula